Surface wave Cherenkov maser based on a periodic lattice - Konoplev, I; Fisher, L; Cross, A; Phelps, A; Ronald, K; Robertson, C (2010)
The excitation of a surface wave cavity based on a two-dimensional periodic structure by an energy source, such as relativistic electrons, results in stimulated, single frequency coherent emission. A high-Q cavity has been achieved via a resonant coupling between surface waves and volume waves. The concept of a Cherenkov maser based on the surface wave cavity is discussed and results of numerical studies presented. Links between the model described and the concept of a surface plasmon amplifier, which has been recently introduced are described. © 2010 American Institute of Physics.